Base-assisted transmetalation enables gold-catalyzed oxidative Sonogashira coupling reaction - Lizhu Zhang; Wenchao Zhang; Dinghua Li; Rongjie Yang; Zhonghua Xia (iScience, 2024)
Summary: The traditional transition metal catalyzed neutral C(sp)-C(sp2) cross-coupling reaction between a nucleophile and an electrophile is a key technique for the formation of carbon-carbon bonds. Herein, we present a general gold-catalyzed oxidative Sonogashira cross-coupling of arylboronic acids and terminal arylalkynes at room temperature with excellent functional-group tolerance and good chemoselectivity. Moreover, our mechanistic studies suggested a third pathway involving a base-assisted transmetalation between the gold(I) catalyst and aryl boronic acid might predominate in our reaction conditions, rather than the previously assumed oxidation of the gold(I) complex or deprotonation of alkynes.